New sesquiterpenoid and aliphatic glycoside from the roots of Datura metel L. (August 2022) - Liu, Yan; Wu, Dan-Dan; Luo, Yu-Meng; Liu, Guo-Zhen; Yang, Chun-Li; Algradi, Mohammed; Wu, Jia-Tong; Yang, Bing-You; Kuang, Hai-Xue
Abstract: Three new compounds (1–3 ), were isolated from the 70%-EtOH extract of the roots of Datura metel L., along with thirty-six knowns (4–39 ). Their chemical structures were established based on extensive spectroscopic analyses, including HR-ESI-MS, 1 D NMR, and 2 D NMR as well as comparison with the data reported in the literature. Compounds 7, 8, 10, 12, 14, 15, 19 -23, 27, 29, 31, and 34 were isolated from Solanaceae for the first time and compounds 4, 5, 9, 17, 18, and 26 were firstly isolated from the genus Datura . Moreover, compounds 1, 5, 9, 12, 13, 17, 23, 24, 28, 37, and 39 showed potential anti-inflammatory activities (IC50 <45 μM). Graphic Abstract: ga1 Highlights: 3 new and 36 know compounds were isolated from  D. metel. Fifteen compounds were isolated from Solanaceae for the first time and six compounds were firstly isolated from the genus Datura . Compound 5 showed the strongest anti-inflammatory activity.